2021
DOI: 10.3390/cancers13153883
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Patients’ Willingness to Take COVID-19 Vaccination: A Nationwide Multicenter Survey in Korea

Abstract: Considering the high morbidity and mortality of Coronavirus disease 2019 (COVID-19) in patients with malignancy, they are regarded as a priority for COVID-19 vaccination. However, general vaccine uptake rates among cancer patients are known to be lower than in their healthy counterparts. Thus, we aimed to investigate the attitude and acceptance rates for the COVID-19 vaccine in cancer patients and identify predictive factors for vaccination that could be modified to increase vaccine uptake rates, via a paper-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
51
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(76 citation statements)
references
References 28 publications
9
51
2
Order By: Relevance
“…However, the acceptance rate was much lower than a previous anonymous cross-sectional survey among adults conducted in China (89.5%) [31] . Actually, the distrust towards the COVID-19 vaccine seems to be a worldwide phenomenon: in Korea, among cancer patients who were willing to take the COVID-19 vaccine, only 46.7% trusted its effectiveness [57] ; in Poland, 44.4% of cancer patients questioned the usefulness of COVID-19 vaccines [58] .…”
Section: Discussionmentioning
confidence: 99%
“…However, the acceptance rate was much lower than a previous anonymous cross-sectional survey among adults conducted in China (89.5%) [31] . Actually, the distrust towards the COVID-19 vaccine seems to be a worldwide phenomenon: in Korea, among cancer patients who were willing to take the COVID-19 vaccine, only 46.7% trusted its effectiveness [57] ; in Poland, 44.4% of cancer patients questioned the usefulness of COVID-19 vaccines [58] .…”
Section: Discussionmentioning
confidence: 99%
“…22,23 At this time of uncertainty, increased misconceptions and apprehensions about vaccine safety and efficacy, negative attitudes towards vaccination, and fear of unforeseen side effects may result in vaccine hesitancy leading to undermining efforts to reduce the impact of COVID-19 and these misbeliefs are thought to be pronounced in cancer patients. 24,25 The main factors that determine an individual's intent to take the COVID-19 vaccine include perceived severity of the illness, perceived susceptibility to the disease, perceived benefits that the person is likely to obtain as a result of the vaccine, perceived barriers, and information and knowledge about the disease and the vaccine. 26,27 Therefore, assessing cancer patients' awareness of and readiness to receive the COVID-19 vaccine along with the main factors which could increase the likelihood of receiving the vaccine will help develop and implement effective strategies in promoting the COVID-19 vaccine and decrease the recent alarming increase in COVID-19 new cases among cancer patients.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies worldwide have documented varying rates of vaccine hesitancy among oncological patients that can be as high as 59%. 2 , 3 , 4 , 5 , 6 , 7 , 8 The increased risk of infection and COVID-19 associated morbidity and mortality in cancer patients, as well as the emergence of new SARS-CoV-2 variants that keep imposing a tremendous strain on healthcare services worldwide, makes the high hesitancy rate towards COVID-19 immunization a matter of great concern.…”
mentioning
confidence: 99%
“…These concerns, as well as the lack of information regarding the safety and effectiveness of COVID-19 vaccines, are among the most commonly associated factors with vaccine hesitancy in the oncological population. 1 , 3 , 4 , 5 , 6 , 7 , 8 Fortunately, the majority of studies assessing COVID-19 vaccine hesitancy among these patients have found that the most common reasons that could motivate hesitant patients to get vaccinated were being recommended by their oncologists/treating physician and having more information regarding COVID-19 vaccines’ effectiveness and safety. 3 , 4 , 5 , 6 , 8 In accordance with these findings, our research group aimed to evaluate if an educational webinar could influence the knowledge and attitudes towards COVID-19 vaccination in cancer patients.…”
mentioning
confidence: 99%
See 1 more Smart Citation